Therapeutic Targeting of Rab GTPases: Relevance for Alzheimer’s Disease - Kate L. Jordan; David J. Koss; Tiago F. Outeiro; Flaviano Giorgini (Biomedicines, 2022)
Rab GTPases (Rabs) are small proteins that play crucial roles in vesicle transport and membrane trafficking. Owing to their widespread functions in several steps of vesicle trafficking, Rabs have been implicated in the pathogenesis of several disorders, including cancer, diabetes, and multiple neurodegenerative diseases. As treatments for neurodegenerative conditions are currently rather limited, the identification and validation of novel therapeutic targets, such as Rabs, is of great importance. This review summarises proof-of-concept studies, demonstrating that modulation of Rab GTPases in the context of Alzheimer’s disease (AD) can ameliorate disease-related phenotypes, and provides an overview of the current state of the art for the pharmacological targeting of Rabs. Finally, we also discuss the barriers and challenges of therapeutically targeting these small proteins in humans, especially in the context of AD.